Pengaruh penggunaan selebgram pada sikap konsumen dalam membangun minat beli untuk melakukan pembelian secara online - Maiyulia Nurman; Yunita Engriani (Universitas Negeri Padang, 2020)
This study aims to analyze: (1) the effect of using a selebgram as an endorsement on purchase intention (2) the effect of consumer attitudes on purchase intention. This type of research is a causative descriptive study. This research was conducted in the city of Padang. The population in this study were students of Padang State University who have an Instagram account. The sample used was 150 people using purposive sampling technique. The type of data in this study is primary data. Data were collected through questionnaires and analyzed using SPSS version 16. The results of this study indicate that: (1) endorsement has a positive and significant effect on purchase intention (2) consumer attitudes have a positive and significant effect on purchase intention. Keywords: Endorsement, attitude, intention